Women as extension advisors - Johnson A. Adebayo; Steven H. Worth (Research in Globalization, 2022)
Extension plays very significant roles in enhancing agricultural production and community development initiatives in South Africa. However, sustainable agriculture, rural livelihood sustainability and food insecurity at household level are still of great concern and continue to be substantial challenges for the country's rural dwellers. While a framework for reform was developed to revitalize extension services in the country, the framework falls short in addressing gender issues in extension services. Given the significant role women play in agriculture in South Africa, this oversight compromises the effective attainment of the goals of extension. The review was undertaken to gain insight into the level of involvement of women as agricultural extension advisors and the challenges they face. Drawing from relevant published works, the paper examines the degree to which women and men jointly participate as extension advisors, with reference to South Africa. This paper argues that increased participation of women as extension advisors can help reposition agricultural extension to more effectively facilitate programs to deliver better and more direct impacts on reducing hunger and ensuring human nutrition and food security.
Keywords: 330; Agricultural extension service; Food security; Gender; Sustainable agriculture; Sustainable rural livelihood; Women extension advisors